PENENTUAN CADANGAN PREMI DENGAN METODE PREMIUM SUFFICIENCY PADA ASURANSI JIWA SEUMUR HIDUP JOINT LIFE - PERMATASARI, NI PUTU MIRAH; WIDANA, I NYOMAN; SARI, KARTIKA (E-Jurnal Matematika, 2016)
The aim of this research was to get the formula of premium reserves through the premium sufficiency method. Premium reserve is the amount of fund that is collected by the insurance company in preparation for the claim’s payment. Premium sufficiency method is gross premium calculation. To construct that formula, this research used Tabel Mortalitas Indonesia (TMI) 2011, interest rate 2.5% and cost of alpha %. Based on simulation result in men premium reserve value of age 1 of 56 years propotional with insured periods, but after56 years enhancement of premium reserve value.
Keywords: Joint Life Insurance; Premium Reserve; Premium Sufficiency